Supervision of the Competent Court on Decisions of Arbitration Provisions in Jordanian Law Comparative Study - AL- hroot, Suhayb Ali (Dirasat: Shari’a and Law Sciences, 2020)
This study aimed to identify the judicial control imposed on arbitration judgments, through the identification of legislative texts, as well as the Control imposed by the Constitutional Court under its supervision to monitor the constitutionality of laws, which is the practice of the United Arab Emirates, which established the Supreme Federal Court; however, they have not played a greater role in judicial control over the constitutionality of laws, as their work is related to appeals referred to them by the higher courts or through legislative councils. The role of the court of Appeal, as referred to in the arbitration law of the Hashemite Kingdom of Jordan or the arbitration section of the Civil Procedure Law in the United Arab Emirates, is to uphold the judgements issued, or to consider cases related to the invalidity of those judgments, and we have shown that this, negatively and positively detracts from the rights of the parties to the dispute in relation to public interests. The study recommended the following: work to amend the Jordanian arbitration law in force in the text of Article (51). The terms should be unified in the texts of articles (54,51) with respect to the terms (ratification and implementation). There should be a strengthening of the concept of judicial control. There should be a constitutional amendment aimed at strengthening the concept of judicial control, but the concept should be subjective, far from the concept of judicial referral from the courts.